THE NEO-REALISM IN AUKUS - Adelia Alviani; Rodon Pedrason; Sudibyo (CV. AFDIFAL MAJU BERKAH, 2023)
Indo-Pacific is a very crucial region as many of defense activities from many countries are happening here. As the U.S., United Kingdom and Australia see the importance of the region they then created an alliance to create a free and open Indo-Pacific and make it as a region that is free from coercion and respects human rights. This security arrangement also will provide Australia with nuclear-powered submarines for their defense capabilities. However, this raised concern among many parties that believed there are personal reasons behind the establishment of AUKUS. In short, AUKUS is a media to achieve and protect their national interest. This is in line with neo-realism theory that believed the main goal of every states is to survive and they will create alliances in crucial time. Hence, this paper will discuss the neo-realism in AUKUS. This paper is using a qualitative-descriptive method to better explain neo-realism in AUKUS.